A serological survey and the diagnosis of pseudorabies virus among pigs in Argentina - Echeverría, María Gabriela (1990)
An enzyme linked immunosorbent assay (blocking ELISA) was used to detect antibodies to pseudorabies virus (PRV) in serum samples from 5955 pigs. The results of this test indicated that 10.5% of the samples were positive to pseudorabies. Virus neutralization (VN) test was used as a confirmatory test on 207 positive and 191 negative sera respectively. Using the VN test as standard, the ELISA showed a relative specificity and sensitivity of 88.8% and 98.9%, respectively. An outbreak of pseudorabies was also studied by virological, immuno-histochemical and in situ nucleic acid hybridization methods.